STRATEGI DAYA TARIK CELEBRITY ENDORSE, TRUST, DAN CUSTOMER KNOWLEDGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SEPEDA MOTOR HONDA (SIDOARJO) - Faridatul Nur Afifah; Lilik Indayani (Journal of Economic and Economic Policy, 2024)
The purpose of this research is to determine the influence of celebrity endorsement, trust, and customer knowledge on purchasing decisions for Honda motorbikes. This research uses quantitative methods with a population of Honda motorbike users in Sidoarjo and this sample consists of 100 respondents. The sampling technique uses nonprobability sampling with purposive sampling. Data collection methods include interviews and questionnaires. Questionnaire using Google Form online. The data analysis technique uses a Likert scale and uses multiple linear regression analysis with the help of the SPSS program.